Measurement of CP asymmetries in D±→[eta]'π± and D±s→[eta]'π± decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kecke, Matthieu; et al. (Physics letters, 2017)
D±→η′π± and Ds±→η′π± decays is performed using proton-proton collision data, corresponding to an integrated luminosity of 3 fb−1, recorded by the LHCb experiment at centre-of-mass energies of 7 and 8 TeV. The measured CP-violating charge asymmetries are ACP(D±→η′π±)=(−0.61±0.72±0.53±0.12)% and ACP(Ds±→η′π±)=(−0.82±0.36±0.22±0.27)%, where the first uncertainties are statistical, the second systematic, and the third are the uncertainties on the ACP(D±→KS0π±) and ACP(Ds±→ϕπ±) measurements used for calibration. The results represent the most precise measurements of these asymmetries to date.
LHCb collaboration: R. Aaij, P. d’Argent, S. Bachmann, S. Braun, A. Comerma-Montells, M. De Cian, S. Esen, D. Gerick, E. Gersabeck, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, A. Piucci, M. Stahl, S. Stemmle, U. Uwer, A. Zhelezov [und weitere]
Im Titel sind "+" und "-" untereinander geschrieben: "-" tiefgestellt, "+" hochgestellt
Im Titel sind "±" und "s" untereinander geschrieben: "s" tiefgestellt, "±" hochgestellt
Im Titel wird "eta" als griechischer Buchstabe dargestellt
Gesehen am 20.10.2020